TI_GERICHTE 12.2020.154 vom 24. Juni 2021 , Contratto d'appalto - mercede - onere di allegazione e contestazione - TI Tribunale d'appello (2021)
Contratto d'appalto - mercede - onere di allegazione e contestazione